Souls under Siege : Stories of War, Plague, and Confession in Fourteenth-Century Provence - Archambeau, Nicole (Book collections on Project MUSE., 2021)
"Between 1343 and 1363, people in Europe endured two waves of plague and surging mercenary violence. Plague killed an estimated 1/3 of the population while tens of thousands of mercenaries fought in the Hundred Years War, raiding and occupying towns during lulls. This book shows that many people understood both plague and war as spiritual sicknesses that revealed excessive sin" --